How children learn to be healthy - Tinsley, Barbara J., 1950- (International studies on child and adolescent health., 2003)
The goal of this book is to explore the ways in which health behavior develops in childhood, in the context of childhood socialization processes. The book reviews the historical and contemporary perspectives utilized in portraying the dynamics of children's physical health, a developmental analysis of children's and parents' attitudes and behavior concerning children's health, the role of parents, schools, and the media in influencing children's health attitudes and behavior, and how health attitudes, behaviors, and outcomes are affected by the social ecology of children's rearing environments.